PERILAKU KOMUNIKASI SIMBOLIK GAY DI KOTA AMBON SUATU PENDEKATAN FENOMENOLOGI - Amelia Tahitu; Demsy Wattimena; Ayu Irawan (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to find out and explain the subjective experience and awareness of gay communication which is understood from gay symbolic communication behavior in Ambon City. The method used is a qualitative method with a phenomenological tradition. The research subjects were 10 gay informants who were selected purposively with the criteria of being able to articulate their own lives through subjective communication experiences. Data analysis technique using phenomenological data analysis method. The research results found that 1). Gay communication behavior through their communication actions occurs through their mutual agreement (gay) both verbal and non-verbal (symbolic) communication. This is done in order to create social interaction and/or social relationships between them (gays), 2). Gay verbal communication behavior with friends in the community and with outside groups, shows a shared understanding of verbal messages such as; Akika which means me, Adinda which means there, Organda which means person, plenary which means perfect and so on, 3). The symbolic communication behavior of gays with friends and outside groups through slang with the characteristics of communication between them (gays), has been understood together through body gestures that look feminine, and greatly influences their actions towards other people, such as extended non-verbal (symbolic) messages. and has been used by friends outside the group such as; cyin (darling), eto (lying), racik gravy (talking excessively), krisdayanti (Christian), musdalifa (Islam) which are used by people's names, 4). The meaning of gay symbolic communication verbally and non-verbally is showing their true identity as gay, through fashion appearance (clothing), flashy colors and accessories that look very dominant. However, in gay communication with their families, there are gays who still hide themselves or hide their identity, so that their family does not know, but there are other gays who do not hide their identity when communicating with their family or with outside groups. And suggestions/recommendations are 1). It is hoped that the people of Ambon City can understand and know them (gays) and their community, through symbolic communication behavior, so that there are no misunderstandings in communicating with them (gays), 2). The Ambon City Government, or policy makers, can know and understand the characteristics, characteristics, and numbers of their (gay) communities, so that they can have information and their (gay) social status in Ambon City.